2002
DOI: 10.1177/073401680202700103
|View full text |Cite
|
Sign up to set email alerts
|

Using Inmate Survey Data in Assessing Prison Performance a Case Study Comparing Private and Public Prisons

Abstract: The public sector needs to monitor the performance of the private prisons, and it is necessary to conduct the monitoring as objectively as possible. This article demonstrates that an often overlooked source of data, surveys of inmates, can be used to differentiate prisons on such Was a gag activity, and security, sanitation, and food service delivery. Hierarchical line models were used to generate the prison performance measures. We also show that inmates and staff largely agreed in in their assessments of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 19 publications
4
70
0
2
Order By: Relevance
“…As far as we know, only Camp et al (2002) found that perceptions of prison staff and inmates on the sanitation in the dining hall and the housing unit are highly congruent. In order to examine whether connecting of the two surveys can also yield meaningful knowledge here, we test the analogy between a couple of staff and inmate scales dealing with the same subject (perceptions of contacts between staff and inmates and perceived hygiene).…”
Section: Pairing Survey Results and Hierarchical Modelsmentioning
confidence: 90%
“…As far as we know, only Camp et al (2002) found that perceptions of prison staff and inmates on the sanitation in the dining hall and the housing unit are highly congruent. In order to examine whether connecting of the two surveys can also yield meaningful knowledge here, we test the analogy between a couple of staff and inmate scales dealing with the same subject (perceptions of contacts between staff and inmates and perceived hygiene).…”
Section: Pairing Survey Results and Hierarchical Modelsmentioning
confidence: 90%
“…With the exceptions of Camp et al (2002a), Camp et al (2002b), and Logan (1996), very few studies have compared the social climate of different prisons. Using a series of management-related performance measures derived from surveys of staff and institutional records, Logan (1996) compared the private operations of a prison with its previous state agency operations.…”
Section: Comparisons Between Different Prisonsmentioning
confidence: 99%
“…With regard to the perceived safety of the environment, only one public prison (FCI Yazoo City) was rated as less safe than the private prison. In subsequent analyses, Camp et al (2002a) examined inmate responses to the prison environment in the same four prisons (three public and one private), concluding that prisoners and staff largely agreed in their assessments of the prisons.…”
Section: Comparisons Between Different Prisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that respondents would report a state of affairs while knowing reality is different. However, other research suggests that survey results in prisons (both inmate and staff) vary in a systematic way across facilities (Camp, 1999;Camp et al, 2002;Molleman, 2008;Molleman & Leeuw, 2012). Survey data have been shown to be consistent with official prison records (Dagget & Camp, 2009;Molleman, 2011).…”
Section: Closing Remarksmentioning
confidence: 99%